2023
DOI: 10.3390/ijms24031990
|View full text |Cite
|
Sign up to set email alerts
|

Combined Fluorescence Fluctuation and Spectrofluorometric Measurements Reveal a Red-Shifted, Near-IR Emissive Photo-Isomerized Form of Cyanine 5

Abstract: Cyanine fluorophores are extensively used in fluorescence spectroscopy and imaging. Upon continuous excitation, especially at excitation conditions used in single-molecule and super-resolution experiments, photo-isomerized states of cyanines easily reach population probabilities of around 50%. Still, effects of photo-isomerization are largely ignored in such experiments. Here, we studied the photo-isomerization of the pentamethine cyanine 5 (Cy5) by two similar, yet complementary means to follow fluorophore bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…For SMLM with cyanine dyes, it has recently been reported that photoisomerized states of Cy5 with redshifted excitation spectra may lead to unwanted FRET-mediated excitation transfer between closely (<10 nm) located non-photoisomerized and photoisomerized fluorophores. 36 Thus, in the context of SMLM, the fact that such photoisomerized states also can show redshifted emission, as very recently shown for Cy5, 53 and shown for NIR cyanines in this work, makes it necessary to also account for this emission source in the analyses of the resulting blinking. Beyond SMD and SRM experiments, since the redshifted emissive state is generated already at relatively low excitation intensities ( Figure 3 D), excitation and emission spectra of NIR cyanine dyes can be expected to be altered in a range of experiments.…”
Section: Discussionsupporting
confidence: 55%
“…For SMLM with cyanine dyes, it has recently been reported that photoisomerized states of Cy5 with redshifted excitation spectra may lead to unwanted FRET-mediated excitation transfer between closely (<10 nm) located non-photoisomerized and photoisomerized fluorophores. 36 Thus, in the context of SMLM, the fact that such photoisomerized states also can show redshifted emission, as very recently shown for Cy5, 53 and shown for NIR cyanines in this work, makes it necessary to also account for this emission source in the analyses of the resulting blinking. Beyond SMD and SRM experiments, since the redshifted emissive state is generated already at relatively low excitation intensities ( Figure 3 D), excitation and emission spectra of NIR cyanine dyes can be expected to be altered in a range of experiments.…”
Section: Discussionsupporting
confidence: 55%